The search for life in the Solar System passes through the Astrobiology Laboratory of the INAF-Arcetri Astrophysical Observatory - Fornaro, Teresa; Brucato, John Robert (Il Colle di Galileo, 2022)
The scientific activity of the Astrobiology Laboratory of the Arcetri Astrophysical Observatory spans from research on the origin of life to simulations of astrobiologically relevant processes, the search for life in the Solar System and the development of planetary exploration technologies, along with the analysis of extraterrestrial samples brought back to Earth and the development of planetary protection methodologies and facilities for the curation of extraterrestrial samples.